Sesar Lembang dalam Perspektif Sains dan Spiritualitas Mahasiswa Islam - Iya Aini Azzahra; Rafa Via Syafutra; Irgi Rasyda; Ahmad Faqihuddin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to describe the perceptions of Muslim university students toward the Lembang Fault phenomenon from the perspectives of science and Islamic spirituality. The research employs a descriptive quantitative method with 30 Muslim students from various universities in Bandung as respondents. Data were collected through an online questionnaire containing questions about scientific knowledge and the spiritual meaning of potential disasters. The results show that 86.7% of respondents recognize the Lembang Fault as an active fault, 90% consider scientific knowledge important, and 93% believe that science and spirituality should complement each other. Furthermore, 95% of respondents believe that Islamic values such as patience (sabr), trust in God (tawakkul), and prayer (du‘a) can strengthen mental preparedness in facing disasters. These findings emphasize the importance of integrating science and faith as the foundation for disaster preparedness. The study recommends implementing disaster education based on Islamic values in higher education to foster students’ scientific and spiritual resilience.